2012
DOI: 10.1021/ie202864n
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Assisted Degradation of Dye Pollutants in Ag3PO4 Suspension

Abstract: Sunlight-induced photodegradation of rhodamine B over Ag3PO4 has been observed. Nanosized Ag3PO4 was synthesized by a facile ion-exchange route. X-ray powder diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, the Brunauer–Emmett–Teller surface area, UV–vis diffuse reflectance spectroscopy and photoluminescence spectra were employed to investigate the phase structure, morphology and optical property of the Ag3PO4 product. Nearly 100% of rhodamine B was degraded after a very short irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
120
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(137 citation statements)
references
References 37 publications
15
120
0
2
Order By: Relevance
“…The results (Fig. 7c) certified that h + is the main oxidative species in pristine Ag 3 PO 4 material, which is consistent with the previous literature [44]. Based on the above analysis, it can be concluded that the photooxidation process occurring on the surface of Ag 3 PO 4 /HAp-773 sample may involve the direct reaction of the pollutants with strong oxidizing superoxide radicals and holes.…”
Section: The Mechanism Of the Enhanced Photocatalytic Activitysupporting
confidence: 90%
“…The results (Fig. 7c) certified that h + is the main oxidative species in pristine Ag 3 PO 4 material, which is consistent with the previous literature [44]. Based on the above analysis, it can be concluded that the photooxidation process occurring on the surface of Ag 3 PO 4 /HAp-773 sample may involve the direct reaction of the pollutants with strong oxidizing superoxide radicals and holes.…”
Section: The Mechanism Of the Enhanced Photocatalytic Activitysupporting
confidence: 90%
“…Dye contamination has become a major factor that contributes to water quality deterioration, and poses a potential hazard to living organisms due to the toxic, carcinogenic and mutagenic properties of dyes and their by-products [6][7][8][9][10]. Hence, the removal of organic dye pollutants from the wastewater becomes very essential.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated E CB and E VB edge positions for Ag 3 PO 4 are 0.49 and 2.85 eV, and for CoFe 2 O 4 are 0.14 and 1.9 eV, respectively, which are close to previous reported values. 58,59 On the basis of the above results and the detection of active species in the photodegradation process, a possible photocatalytic mechanism for dye photodegradation using Ag 3 PO 4 / CoFe 2 O 4 nanocomposite has been proposed as follows and illustrated in Fig. 12.…”
mentioning
confidence: 99%